Analisis Pendapatan Petani Padi Sawah Di Kelurahan Sawidago Kecamatan Pamona Utara - Jef Vebrianto Perori; Charis Elfis Fajar Sangkide; Fredrik Bastian Kawani (Interdisciplinary Journal (IDe), 2023)
This study aims to determine the net income (profits) obtained by rice farmers in the village of Sawidago, Pamona Utara sub-district each time. The data used are primary data and secondary data obtained through direct interviews with respondents and through the village office, PPL officers and literature. The analysis used in this study quantitatively is to calculate the net income (profit) that is obtained on average for each paddy rice farmer. The results showed that the average net income of rice farmers was Rp. 2.179.250 each harvest. This figure proves that farming in Sawidago village has been able to provide benefits. But these benefits still cannot meet all the family's needs.